Pengaruh Sistem Akuntansi Keuangan Daerah, Transparansi Publik dan Aktivitas Pengendalian terhadap Akuntabilitas Keuangan pada Badan Keuangan Daerah Provinsi Kepulauan Bangka Belitung - Tasya Kirana Maharani Putri; Suhaidar Suhaidar; Nur Ahmad Ricky Rudianto (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Financial accountability refers to the obligations and openness of an entity, be it a government, organization, or company, in managing, reporting, and being accountable for the use of its funds and financial resources. This research aims to analyze and determine the influence of the regional financial accounting system, public transparency, financial control and accountability activities in the Regional Financial Agency of the Bangka Belitung Islands Province. This study uses a quantitative approach. The sample in this study was 140 respondents. The data analysis technique is multiple regression analysis. Based on research results, regional financial accounting systems have no effect on financial accountability, public transparency has no effect on financial accountability, and control activities have an effect on financial accountability.